1991
DOI: 10.1093/genetics/129.2.501
|View full text |Cite
|
Sign up to set email alerts
|

The maternally inherited regulation of P elements in Drosophila melanogaster can be elicited by two P copies at cytological site 1A on the X chromosome.

Abstract: Two P elements, inserted at the cytological site 1A on an X chromosome from an Drosophila melanogaster natural population (Lerik, USSR), were isolated by genetic methods to determine if they are sufficient to cause the P cytotype, the cellular condition that regulates the P family of transposable element. The resulting "Lerik P(1A)" line (abbreviated "Lk-P(1A)") carries only one P element in situ hybridization site but genomic Southern analysis indicates that this site contains two, probably full length, P cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(24 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Such progeny are normally sterile because P elements are mobilized at high levels in their germline causing massive cell death (NIKI and CHIGUSA 1986). Repression of Pelement mobility is indicated by an increase in the proportion of fertile female progeny (ROBERTSON and ENGELS 1989;RONSSERAY et al 1991;GLOOR et al 1993 In these matings, a P[wactKP] element was located either on the X chromosome or was homozygous on either the second or third chromosome. Three or four males from the w; Hanvich strain were mated with a single virgin female.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Such progeny are normally sterile because P elements are mobilized at high levels in their germline causing massive cell death (NIKI and CHIGUSA 1986). Repression of Pelement mobility is indicated by an increase in the proportion of fertile female progeny (ROBERTSON and ENGELS 1989;RONSSERAY et al 1991;GLOOR et al 1993 In these matings, a P[wactKP] element was located either on the X chromosome or was homozygous on either the second or third chromosome. Three or four males from the w; Hanvich strain were mated with a single virgin female.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…If laboratory lines differ in these alleles, this can cause between line variability in transposition rates. In the latter scenario, different lines may have inherited copies of TEs with differences in the propensity to transpose ( Ronsseray et al 1991 ; Kim et al 1994; Nuzhdin et al 1997 ; Nuzhdin 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early work on TE insertions concluded that on average, they are likely to be neutral or deleterious ( Doolittle et al 1980 ), and for a long time, active TEs variants were thought to be rare in natural populations ( Kaplan et al 1985 ; Ronsseray et al 1991 ; Brookfield 1991 , 1996; Nuzhdin et al 1997 ). Alternatively, it was not active TEs that are rare but individuals with “permissive” genetic backgrounds, such that TEs would remain inactive until encountering a permissive genetic background and then proliferate ( Nuzhdin 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…These clusters represent a genetic footprint of TEs already encountered by the host: invading copies can insert into existing clusters or create de novo ones [75][76][77], thus contributing to establish an 'immunity' system against TE invasions. This mechanism is highly efficient: evidence suggests that the insertion of a single TE copy in a piRNA cluster might be sufficient to silence all the similar sequences [78][79][80]. Since piRNA clusters are enriched in old degraded TE copies, these might have been co-opted to mediate the silencing of full-length elements ( [81]; reviewed in [82]).…”
Section: Te Relics Safekeepers Of the Germlines?mentioning
confidence: 99%